Historical state-level data on U.S. public school systems from 1919/20 to 1973/74 - Katrina M. Walsemann; Emily Abbruzzi; Heide M. Jackson; Pallavi Tyagi; Jennifer A. Ailshire (Scientific Data)
Abstract There is growing interest in understanding how exposure to education contexts and quality shapes wellbeing, particularly in later life. Although public investment in education expanded significantly during much of the 20th century, electronic data on U.S. public education systems before 1975 remain limited. In this paper, we introduce the State Education Contextual Data Resource (S-ECDR), a publicly available dataset that provides state-level education context measures from 1920–1974. We describe the procedures used to construct S-ECDR from historical reports, outline the available measures of state-level education context, and discuss key considerations for linking the dataset with other population-based surveys. Data from the S-ECDR indicate substantial improvements in public education systems over the 20th century but also persistent disparities across states, with southern states investing less in their education systems. The S-ECDR can be linked to population-representative survey data to examine how education contexts shape well-being in midlife and older adulthood.